2006
DOI: 10.1080/14634980600721474
|View full text |Cite
|
Sign up to set email alerts
|

Coastal erosion and reclamation in Malaysia

Abstract: Reclamation, a human activity that can transform an entire environment in a relatively short time, epitomizes one of the pinnacles of engineering achievement—creation of new landmass. As demonstrated by the construction of the Chek Lap Kok and Kansai airports in Hong Kong and Japan respectively, whole new islands can be created in this way and, in the process, landscapes, eco-systems and livelihoods could be altered. Considering the potential and major implications, reclamation projects call for a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“…The history of land reclamation in Zhoushan can be traced back to 1000 years ago. Reclamation can completely change the natural environment entirely in a very short period (Ghazali 2006). With increasing reclamation projects, the vegetation cover rate dropped, and the area of impervious surface grew (Lautenbach et al 2011;Ruiz-luna 2014).…”
Section: Ecosystem Services In the Reclamation Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The history of land reclamation in Zhoushan can be traced back to 1000 years ago. Reclamation can completely change the natural environment entirely in a very short period (Ghazali 2006). With increasing reclamation projects, the vegetation cover rate dropped, and the area of impervious surface grew (Lautenbach et al 2011;Ruiz-luna 2014).…”
Section: Ecosystem Services In the Reclamation Areamentioning
confidence: 99%
“…With increasing reclamation projects, the vegetation cover rate dropped, and the area of impervious surface grew (Lautenbach et al 2011;Ruiz-luna 2014). Degradation of water quantity and quality cannot be ignored, especially on some small islands where groundwater conditions have completely changed (Ghazali 2006;Guo and Jiao 2007;Hu and Jiao 2014;Ni et al 2019). Land reclamation also reduced the sediment accumulation rate, thus preventing new mud flats, which may provide essential habitats and ecosystem services (Ghazali 2006;Mai and Bartholomä 2000).…”
Section: Ecosystem Services In the Reclamation Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Mangrove growth faster in balanced of nutritional status [3]. However, across the world, mangrove forest is facing severe coastal erosion caused by deforestation and land reclamation for development, livelihoods and agriculture farms to meet human's needs [4]. These activities changed the mangrove ecosystem as well as its ecological functions.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that, 52% of the coastline in the east coast of Peninsular Malaysia is being eroded and in the west coast, 50% of the coastline is being eroded [3]. The recent study has revealed that about 29% of the total of 4800km of Malaysia shoreline was subjected to varying degree of erosion [4].…”
Section: Introductionmentioning
confidence: 99%